X-linked adrenoleukodystrophy in a pediatric patient: A case report - Graciela A. López-Uriarte (Permanyer, 2021)
X-linked adrenoleukodystrophy (X-ALD) is a peroxisomal disorder caused by mutations in the ABCD1 gene leading to the accumulation of very long-chain fatty acids. A 6-year-old male started his condition 6 months ago with developmental regression and loss of visual acuity. Physical examination showed hyperpigmentation in the folds and strabismus of the left eye; ophthalmoscopy showed bilateral optic nerve atrophy, decreased osteotendinous reflexes, and ataxic gait. Adrenal function was evaluated, finding elevated adrenocorticotropic hormone (ACTH). It was decided to start hormone replacement therapy, and he was sent to the department of genetics, who started treatment with Lorenzo’s oil. He presented an infectious condition requiring hospitalization; 1 week after this event, he attended pediatric endocrinology with new ACTH results showing a poor response to treatment, doses were adjusted. Three months later, he came with a deterioration of symptoms, so a new treatment was started and new studies were requested. The clinical presentation, in this case, is atypical to X-ALD. The progression of the disease is rapid with characteristics similar to MLD, which implies a greater challenge in the diagnosis.